Effects of the use of crystalline admixtures on alkali-aggregate reaction and water absorption of mortars - Parreira Vilela, Hygor Thairony; Teixeira Filho, Marcos G.; Campos Neto, Tiago Ferreira (Revista ALCONPAT, 2021)
This article aims to evaluate the effectiveness of different contents of crystalline admixture in preventing the alkali-aggregate reaction in mortars. The analysis was carried out by means of accelerated expansion tests method of mortars in parallel with tests of mechanical strength, capillarity, porosity and void ratio. It was observed that the presence of alkaline products in the composition of the admixture significantly increased the initial expansions within the first week. Regarding the results of mechanical strength, water absorption and voids, the product was satisfactory improving the properties of the mortars. In general, the results attest to the effectiveness of the admixture in sealing voids and pores but not in inhibiting the alkali-aggregate reaction.